PERLINDUNGAN HAK CIPTA SENIMAN ATAS PEMBAJAKAN ILUSTRASI DIGITAL DALAM BENTUK NON-FUNGIBLE TOKEN - Amukti, Enggal Triya; Susanti, Erna; Triyana, Lily (JIPRO: Journal of Intellectual Property, 2023)
The development of technology nowadays seems to reach all aspects of life, includes the realm of art, especially digital illustration. However, these developments were not followed by regulatory developments so that there was a legal vacuum in them. This study is intended to analyze the legal vacuum of limiting an act that can be categorized as piracy and legal protection for the creator of the piracy of digital illustrations which are  tokenized in the form of NFT using doctrinal research methods. Based on the results of the study, it is concluded that the Standard of Copyright Ability and substantial similarity can be used as criteria for piracy of digital illustrations. There are still vacancies in the regulations regarding the limitations of piracy of a work and the provisions governing NFT. The copyright protection system for digital illustrations in the current regulations consists of preventive and repressive protection. Due to this legal vacuum, it is hoped that regulation about NFT and fine art can be added, and awareness of all parties can be made to avoid infringement of other people's copyrights.